Effect of Lysine-Fermentation By-Product on Urine pH and Total Urine Bacteria Count in Lactating Sows - K. M. Gourley; J. M. DeRouchey; J. C. Woodworth; M. D. Tokach; S. S. Dritz; R. D. Goodband; K. J. Touchette (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 27 mixed parity sows (Line 241; DNA, Columbus, NE) were used in a lactation study to determine the effect of a lysine-fermentation by-product on sow urine pH and total urine bacteria counts. On d 110 of gestation, females were weighed, blocked by BW and parity, and allotted to 1 of 2 dietary treatments. Dietary treatments included a control (corn-soybean meal lactation diet) or the control diet that was acidified by the addition of 1.75% (as-fed basis) of a lysine-fermentation by-product. The dietary electrolyte balance (dEB) was calculated using the following equation (dEB =[(Na/23) + (K/39.1)] – [(Cl/35.5) + (S/16)] × 10,000). The calculated dEB was 95.9 and -23.7 mEg/kg for the control and acidified diets, respectively. Sows were fed the lysine-fermentation by-product diet from d 110 of gestation until d 10 of lactation, at which point they were switched to the control diet for the remainder of the lactation period. There was no evidence for difference in urine pH (P>0.05) between dietary treatments at d 110 of gestation; however, at farrowing and d 10 of lactation, there was a reduction (P= 0.001) in urine pH in sows fed the lysine-fermentation by-product compared to sows fed the control diet. By weaning (d 19) there was no evidence for differences in urine pH observed among the dietary treatments. There was no evidence for differences (P>0.05) in total bacteria count in urine between sows fed either dietary treatment on d 110 of gestation, farrowing, d 10 of lactation, or weaning. Overall, lowering dEB with the lysine-fermentation by-product resulted in decreased urine pH. Additional research should be conducted with a larger number of sows to determine the impact of lysine-fermentation by-product on indicators of sow farm productivity and profitability.
Keywords: dietary electrolyte balance; sow; lactation